Corrosion inhibitors with reduced odor and emissions

By employing a resin composition with reduced double allyl hydrogen atoms and utilizing a Diels-Alder reaction, the composition addresses the challenges of odor and emission issues in conventional corrosion inhibitors, resulting in a more stable and homogeneous coating with reduced odorous compounds.

JP7669389B2Active Publication Date: 2025-04-28PFINDER KG
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022564761
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-24
Filing Date
2021-04-14
Publication Date
2025-04-28
Estimated Expiration
2041-04-14

AI Technical Summary

Technical Problem

Conventional corrosion inhibitors for cavity and bottom protection in automotive components face challenges such as long drying times, insufficient drying, high process costs, and the generation of odorous decomposition products like short-chain aldehydes and carboxylic acids during oxidative crosslinking.

Method used

The use of a composition comprising a resin with a reduced number of molecules containing double allyl hydrogen atoms, applied with a wet film thickness of 40 μm to 1,000 μm, which undergoes a Diels-Alder reaction to reduce oxidative cleavage and subsequent odor and emission issues.

Benefits of technology

This approach significantly reduces the formation of odorous compounds, thereby minimizing emissions and improving the stability and homogeneity of the corrosion inhibitor coating, leading to enhanced thermal stability and prolonged useful life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669389000001
    Figure 0007669389000001
  • Figure 0007669389000002
    Figure 0007669389000002
  • Figure 0007669389000003
    Figure 0007669389000003
Patent Text Reader

Abstract

The present invention relates to the use of a composition for producing a corrosion inhibitor for cavity sealing or bottom protection of a part with reduced odor and emissions, the composition including a resin, the resin including a plurality of molecules, the plurality of molecules including molecules without double allylic hydrogen atoms, and the corrosion inhibitor with reduced odor and emissions is applied to the part at a wet film thickness of 40 μm to 1,000 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to corrosion prevention of solid surfaces. In particular, the present invention relates to the use of a composition for producing a corrosion inhibitor with reduced odor and emissions for use in cavity sealing or bottom protection of parts, particularly automotive parts. In this regard, the composition includes a resin. The resin includes a plurality of molecules. The plurality of molecules includes molecules that do not have double allylic hydrogen atoms. The composition is applied to the part at a wet film thickness of 40 μm to 1,000 μm. [Background technology]

[0002] Corrosion inhibitors, particularly those used for cavity protection (HRC), such as those found in vehicle bodies, are known in the art. Cavity protection agents are particularly well known in vehicle manufacturing, and when applied to, for example, metal substrates, provide good protection against corrosion caused by water, humid air, etc.

[0003] Generally, there are two types of cavity protectants: immersion wax and spray wax. In the prior art, spray-applied cavity protectants typically contain wax and / or resin, functional additives such as corrosion inhibitors, formulation additives such as rheological aids and dispersing aids, and inorganic fillers. These components are dispersed in an aqueous solvent (water-soluble cavity protectants) or a non-polar organic solvent (solvent-containing cavity protectants). Solvent-free, so-called 100% cavity protectants are also available.

[0004] To ensure uniform distribution of sprayed cavity protection agents on a component, low-viscosity products are typically used to ensure uniform application across the component surface and deep penetration into the grooves. While low viscosity is essential for achieving the most uniform application possible, it is also necessary to stop the flow of the cavity protection agent so that it does not drip from the application nozzle opening after being applied to the entire relevant area of ​​the component. Furthermore, depending on the component, a higher or lower viscosity may be required to ensure that the cavity protection agent is distributed throughout the entire component. However, because it is usually impossible to individually adjust the rheology, an average rheology of the material is selected to ensure that the agent is applied as completely as possible to the component without dripping.

[0005] For solvent-based and water-soluble cavity protectants, the necessary viscosity increase after application is achieved by evaporation of the solvent or water. For 100% cavity protectants, this viscosity increase is achieved by increasing the temperature (e.g., 60°C for 1 minute). This increase in temperature induces gelation of the cavity protectant after cooling, known as drop stop, preventing dripping of the cavity protectant and ensuring process reliability. However, the use of an oven poses challenges in terms of energy and investment costs for customers and OEMs. It is also difficult to ensure a consistent temperature increase across all film thicknesses.

[0006] After the solvent evaporates or the cavity protectant gels, a protective film forms on the coated surface to protect against corrosion. Good thermal stability is required to prevent the film from re-liquefying or leaking if the part is reheated during further cavity protection. The corrosion-protective film should have a strength of -20 to +90°C. Solvent-containing and 100% cavity protectants typically achieve heat resistance through chemical crosslinking of the solvent-containing components, such as oxidative crosslinking, or by drying the alkyd resin, which takes approximately 3 to 5 days.

[0007] Overall, the application of the cavity protectant is a two-step process: 1. Application to the target area followed by immediate flow to allow full penetration of the cavity protectant, and if necessary, a controllable increase in viscosity; 2. Chemical cross-linking during / after the viscosity increase to provide long-term thermal stability.

[0008] Traditional 100% cavity protectants have issues with long drying and crosslinking times, often resulting in insufficient drying, and the average rheology of the material is selected to accommodate every individual through-hole and set point. This typically requires a drip line to control dripping of the wet cavity protectant, and masking of components such as sills is also required. This increases the cost of the protection process and often requires manual post-processing to remove cavity protectant residue. Another issue with oxidatively crosslinkable cavity protectants (solvent-based and 100% cavity protectants) is the generation of decomposition products. These are primarily C5-C9 aldehydes and the carboxylic acids formed by their oxidation, which can cause emissions and odors inside the vehicle. While all OEMs have set strict limits, some are difficult to achieve.

[0009] One of the challenges is that smooth application and good thermal stability of corrosion inhibitors, such as those for cavity or bottom protection, can only be guaranteed with one-component mixtures that allow for crosslinking. However, currently used alkyd-based technologies produce emissions and odors. Furthermore, other binder technologies either do not meet the necessary criteria, such as one-component system, non-labeling, shelf stability, and room-temperature crosslinking, or only partially so. Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, an object of the present invention is to provide a composition used to produce a corrosion inhibitor for cavity sealing or bottom protection of parts, which has reduced odor and emissions. Furthermore, a use of the composition for producing a corrosion inhibitor for cavity sealing or bottom protection of parts, which has reduced odor and emissions, is provided. This use solves the above-mentioned problems. Another object of the present invention is to provide a use characterized by reduced emissions, particularly odor. Yet another object is to provide a use of a highly stable composition containing a polyester resin and / or an alkyd resin for producing a corrosion inhibitor for cavity sealing or bottom protection of parts, which has reduced odor and emissions. [Means for solving the problem]

[0011] According to the present invention, the above-mentioned problem is solved by the use of a composition for producing a corrosion inhibitor for cavity sealing or bottom protection of parts, with reduced odor and emissions, which comprises: the composition comprises a resin, the resin comprises a plurality of molecules, the plurality of molecules comprising molecules that do not have double allylic hydrogen atoms; The problem is solved by providing a use characterized in that the composition is applied to a part in a wet film thickness of 40 μm to 1,000 μm.

[0012] In double allylic hydrogen atoms, one hydrogen atom is present at the allylic position of the two double bonds. Therefore, the basic structural feature is having two double bonds and a CHR group between them, where R can be H or any other group. The simplest example of a compound with double allylic hydrogen atoms is 1,4-pentadiene. Another example of a compound with double allylic hydrogen atoms is linoleic acid or linoleic acid esters.

[0013] Molecules with double allylic hydrogen atoms are known to be susceptible to oxidative crosslinking, particularly to the generation of short-chain aldehydes. This can be prevented by reducing the number of molecules with at least one double allylic hydrogen atom. This is preferably done while maintaining crosslinkability, i.e., without reducing the number of (lateral) crosslinkable double bonds. Therefore, these (lateral) crosslinkable double bonds are present in the resin in the form of isolated and / or clustered double bonds.

[0014] The "composition for producing a corrosion inhibitor for cavity sealing or bottom protection of parts with reduced odor and emissions," also referred to in this application as the "corrosion inhibitor," has the properties of reduced odor and emissions of the resin contained therein due to a low content of double allylic hydrogen atoms.

[0015] As mentioned above, there are several ways to reduce the content of double allylic hydrogen atoms. One method is to use one or more resins that do not contain double allylic hydrogen atoms and contain only other crosslinkable groups, such as isolated C-C double bonds and / or clustered C-C double bonds, from the beginning. The proportion of one or more resins with double allylic hydrogen atoms can also be reduced by adding one or more resins that do not contain double allylic hydrogen atoms (molecules that do not contain double allylic hydrogen atoms).

[0016] Alternatively, or in addition, one or more resins (molecules) containing double allylic hydrogen atoms may be subjected to a chemical reaction that removes the double allylic hydrogen atoms (or reduces the content of double allylic hydrogen atoms in the resin), preferably without reducing the number of double bonds or only slightly, so as to maintain sufficient crosslinkability. A preferred example of such a chemical reaction is the Diels-Alder reaction, in which one or both of the C—C double bonds in the double allylic hydrogen group react with a diene, such as cyclopentadiene, as a dienophile.

[0017] As a result, within the scope of the present invention, the formation of odorous compounds, in particular short-chain aldehydes or short-chain carboxylic acids, in particular aldehydes or carboxylic acids having 3 to 9 carbon atoms, e.g., 4 to 8 carbon atoms, 5 to 7 carbon atoms, or 6 carbon atoms, is partially, preferably completely, prevented, resulting in reduced emissions.

[0018] Furthermore, in this study, we discovered that a Diels-Alder reaction occurs when a substituted or unsubstituted 1,3-butadiene (hereinafter referred to as a diene) reacts with a double or triple bond in an unsaturated compound, the first molecule. This double or triple bond in the unsaturated compound acts as a dienophile in this reaction. The ring system formed by the [4 + 2] cycloaddition of the diene to the dienophile has one double bond (addition of the diene to a double bond) or two isolated double bonds (addition of the diene to a triple bond). These double bonds are believed to be capable of contributing to the oxidative crosslinking of the first molecule. Because the double bond formed in the Diels-Alder reaction is within a ring system (substituted cyclohexene or substituted 1,4-cyclohexadiene), subsequent oxidative cleavage of the double bond does not produce short-chain aldehydes, which are responsible for emissions and odors.

[0019] In summary, the inventors have discovered that by reducing the number of molecules containing at least one double allylic hydrogen atom, the oxidative cleavage reactions associated with emissions and odor problems can be at least partially, and preferably completely, prevented without inhibiting or preventing steric crosslinking of the corrosion inhibitor. Furthermore, the reduced proportion or complete absence of short-chain aldehydes / carboxylic acids is believed to result in the corrosion inhibitor having greater homogeneity than conventional corrosion inhibitor coatings. This results in greater coating stability and a longer service life. DETAILED DESCRIPTION OF THE INVENTION

[0020] Resins for use in compositions to produce corrosion inhibitors for cavity sealing or bottom protection of parts with reduced odor and emissions are known.

[0021] The resin may be, for example, an unsaturated polyester, an unsaturated alkyd resin, and / or an unsaturated binder. Moisture-curable prepolymers of the above components and mixtures thereof are also suitable. Particularly preferably, the resin is an unsaturated alkyd resin. Preferably, the resin is a modified resin, and the modified resin has a reduced number of double allylic hydrogen atoms compared to before modification.

[0022] More preferably, the resin is a medium- to long-chain organic compound having at least one functional group selected from the group consisting of an amino group, a carboxy group, and a hydroxy group. Preferred examples of such compounds include alkyd resins, acrylic resins, polyesters, and natural or synthetic oils having OH groups.

[0023] More preferably, the resin is an organic compound having at least one functional group selected from the group consisting of an amino group, a carboxy group, and a hydroxy group. Preferred examples of such compounds include alkyd resins, acrylic resins, polyesters, and natural or synthetic oils having OH groups.

[0024] Particularly preferably, the resin is an ester of an unsaturated fatty acid. Preferably, the ester may be derived from a polyhydric alcohol, more preferably a dihydric alcohol (e.g., ethylene glycol, butanediol, pentanediol, hexanediol, heptanediol, neopentylene glycol, diethylene glycol, and / or triethylene glycol), a trihydric alcohol (e.g., glycerol, trimethylolethane, and / or trimethylolpropane), a tetrahydric alcohol (e.g., pentaerythritol), a hexahydric alcohol (e.g., dipentaerythritol), or a mixture thereof. Particularly preferably, the ester may be an unsaturated fatty acid ester of glycerol. Preferably, the unsaturated fatty acid ester of glycerol may be a triglyceride of an unsaturated fatty acid.

[0025] As used herein, the term "triglyceride" refers to a triple ester of glycerin, a trihydric alcohol, with organic carboxylic acids. The organic carboxylic acids may be the same or different. Thus, the triglyceride may have three ester groups that are the same or different.

[0026] The organic carboxylic acid is preferably a fatty acid, particularly an aliphatic monocarboxylic acid, having from about 4 to 36 carbon atoms, preferably from about 8 to 24 carbon atoms, and more preferably from about 12 to 20 carbon atoms. In this regard, the fatty acid may be unbranched or branched, with unbranched fatty acids being preferred.

[0027] According to the present invention, at least one of the organic carboxylic acids is an unsaturated fatty acid. The unsaturated fatty acid may have one or more unsaturated bonds, for example, 1 to 6 unsaturated bonds. Particularly preferably, the unsaturated bonds are present as conjugated double bonds.

[0028] Monounsaturated fatty acids include undecylenic acid, myristoleic acid, palmitoleic acid, margaroleic acid, petroselinic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, gondoic acid, cetoleic acid, erucic acid, and nervonic acid. Polyunsaturated fatty acids include linoleic acid, calendulic acid, punicic acid, eleostearic acid, stearidonic acid, arachidonic acid, eicosapentaenoic acid, docosadienoic acid, docosatetraenoic acid, docosapentaenoic acid, docosahexaenoic acid, and tetracosahexaenoic acid. Other preferred acids include pelargonic acid, tall oil fatty acid, benzoic acid, p-tert-butylbenzoic acid, versatic acid, abietic acid, stearic acid, isononanoic acid, lauric acid, lactic acid, oleic acid, linoleic acid, palmitoleic acid, gadoleic acid, eleostearic acid, oxoeleostearic acid, erucic acid, gondoic acid, nervonic acid, ricinoleic acid, eicosapentaenoic acid, docosahexaenoic acid, docosapentenoic acid, stearidonic acid, and mixtures thereof.

[0029] The ester of unsaturated fatty acid can also be suitably used in the form of natural oil. Natural oil is oil obtained from plants or animals such as fish. This is particularly preferred because the target compound is obtained from renewable raw materials, which is advantageous in terms of environmental protection. Preferred vegetable oils include linseed oil, castor oil, soybean oil, peanut oil, sunflower oil, safflower oil, rapeseed oil, tung oil, oiticica oil, cottonseed oil, corn oil, safflower oil, wood oil, beet oil, perilla oil, poppy seed oil, castor oil, sesame oil, wheat germ oil, hemp oil, grapeseed oil, walnut oil, varnish oil, currant seed oil, perilla seed oil, or wild rose oil.

[0030] The resins can be easily (chemically) modified, allowing them to be optimized for use in compositions to produce corrosion inhibitors for cavity sealing or bottom protection of components, with reduced odor and emissions. For example, a first component, an alkyd resin with double allylic hydrogen atoms, can be reacted with a second component, a substituted or unsubstituted 1,3-butadiene, to form a Diels-Alder product. In this case, at least one double bond of the first component acts as a dienophile, and a Diels-Alder reaction occurs between the first component and the second component, a substituted or unsubstituted 1,3-butadiene.

[0031] The resin, for example an alkyd resin, is composed of a plurality of molecules. The proportion of molecules having at least one double allylic hydrogen atom is 10 to the total amount of the plurality of molecules. -2 Below 10, preferably -3 For example, 10 -4 Below, 10 -5 Below, 10 -6 Below, 10 -6 It is more preferred that the compound contains no double allylic hydrogen atoms or almost no double allylic hydrogen atoms. Almost no double allylic hydrogen atoms means, for example, 10 -6 ~10 -3 , preferably 5 x 10 -5 ~5×10 -4 , or 10 -5 ~10 -4 This means that the percentage is

[0032] The number of molecules or molecules with double allylic hydrogen atoms is preferably reduced by a Diels-Alder reaction: a molecule with double allylic hydrogen atoms is the first molecule reacting with a second molecule.

[0033] The second molecule is preferably substituted or unsubstituted cyclopentadiene (CPD) or substituted or unsubstituted dicyclopentadiene (DCPD). When CPD or DCPD reacts with the first component, a cleavable double bond is blocked and another double bond is introduced to form a Diels-Alder product, which is oxidatively crosslinkable.

[0034] The resulting Diels-Alder product has the advantage that subsequent reactions, particularly the oxidative crosslinking reaction, do not result in the formation of aldehydes, which are known to be the cause of odors released from corrosion inhibitors.By using the corrosion inhibitors according to the invention, the formation of degradation products, especially short-chain degradation products with strong odors, is suppressed and, if necessary, can even be completely prevented.

[0035] A preferred method for reducing the number of molecules with at least one double allylic hydrogen atom is to perform an upstream Diels-Alder reaction, the resulting product of which is a compound that can be transformed by oxidative cleavage of the unsaturated bond.

[0036] As used herein, the compositions are characterized in that the generation of emissions or odors resulting from oxidative crosslinking of Diels-Alder products is at least partially reduced, preferably completely eliminated.

[0037] Therefore, the coatings obtained by oxidative crosslinking of Diels-Alder products according to the present invention are characterized by higher stability than conventional oxidatively crosslinked binder systems for corrosion protection, likely because the formation of short-chain degradation products, especially the aforementioned short-chain aldehydes or short-chain carboxylic acids, is prevented or significantly limited, resulting in coatings with a highly homogeneous and uniform structure.

[0038] It is clear that different first molecules and / or different second molecules can be used, preferably different first molecules and one type of second molecule, for example dicyclopentadiene, are used.

[0039] In the present invention, it is more preferred that polyunsaturated polyesters, especially polyunsaturated alkyd resins, the composition, reactivity and reaction behavior of which are known to those skilled in the art, are used as the first molecules.

[0040] Dicarboxylic acids such as phthalic acid, phthalic anhydride, and isophthalic acid are also commonly used, which give alkyd resins high hardness and high heat and chemical resistance.

[0041] Aliphatic dicarboxylic acids enhance the resilience of the corrosion inhibitor. For this purpose, one or more of succinic acid, adipic acid, azelaic acid, 2,2,4-trimethyladipic acid, sebacic acid, dodecanedicarboxylic acid, and dimer fatty acids can be used. Flame retardant properties are obtained by adding halogen-containing dicarboxylic acids.

[0042] Preferably, glycerol is used as the polyol. More preferably, glycerol is combined with one or more of pentaerythritol, dipentaerythritol, trimethylpropane, trimethylolethane, sorbitol, and glycol. This increases the molecular weight, allowing for high viscosity, fast drying, or high hardness.

[0043] The amount of fatty acids in an alkyd resin and the number of multiple bonds affect its properties. A high proportion of unsaturated bonds results in fast drying and high gloss, but poor lightfastness. A high amount of fatty acids reduces the degree of polymerization, branching, viscosity, drying speed, and hardness. Fatty acids increase solubility in organic solvents such as gasoline and improve weathering stability. Adding fatty acids in the form of lipids or oils results in transesterification.

[0044] In the art, alkyd resins are classified according to their fatty acid content into short oil alkyd resins (22%-40%), medium oil alkyd resins (40%-60%) and long oil alkyd resins (60%-70%).

[0045] Alkyd resins can be produced by melt-condensing polyols, dicarboxylic acids, and fatty acids at temperatures between 200 and 240°C without the use of a catalyst, along with hydrolysis. A two-step transesterification process using natural fatty acids is also possible. First, a fatty acid glyceride is reacted with a polyol such as glycerol at 240 to 280°C in the presence of a catalyst such as an alkaline earth metal alcoholate. Monoglycerides are obtained as an intermediate product, and in the second step, they are reacted with dicarboxylic acids at 200 to 300°C under an inert gas atmosphere. The reverse route is also possible. In particular, when processing poorly soluble carboxylic acids such as isophthalic acid and terephthalic acid, the first step involves reacting the lipid with a carboxylic acid that also functions as an acid catalyst. The resulting product is then condensed with a polyol. Alkyd resins can also be produced by azeotropic distillation. Xylene is typically used in this process. The properties of alkyd resins can be modified by copolymerization, reaction, or blending with other substances. For example, natural resins enhance gloss and adhesion, phenolic resins enhance water resistance, styrenes enhance drying and chemical resistance, epoxies enhance corrosion resistance, silicones enhance color, gloss, and temperature stability, and diisocyanates enhance drying, hardness, and abrasion resistance.

[0046] The resins, such as unsaturated polyester resins, preferably unsaturated alkyds, or alkyd resins, can be combined and cured by oxidative crosslinking, preferably at elevated temperatures in the presence of atmospheric oxygen. According to Römpp Chemie Lexikon, Georg Thieme Verlag Stuttgart, 9th Revised and Enlarged Edition (1989), alkyd resins formed by the steric crosslinking reaction of alkyds are polyester resins modified with natural fats and / or synthetic fatty acids. They are produced by esterifying polyhydric alcohols, at least one of which is trihydric, with polybasic carboxylic acids. Similarly, fatty acid-free polyesters formed from phthalic acid (anhydride) and glycerol are also considered alkyd resins.

[0047] Oxidative crosslinking or (cross)crosslinking is a reaction that typically occurs during the drying / curing of the composition. This reaction is induced by oxygen, preferably atmospheric oxygen, or by adding an oxygen-containing compound to the composition, which releases oxygen in a controlled manner (e.g., during heating).

[0048] "Drying" is understood to mean allowing the corrosion inhibitor to dry naturally without exposing it to special chemical or physical ambient conditions, e.g., allowing the corrosion inhibitor to dry naturally at room temperature without exposing it to a special or controlled air environment. "Drying" is also understood to mean forced drying, e.g., drying the corrosion inhibitor at elevated temperatures.

[0049] Scheme 1 below is a schematic diagram showing the oxidative crosslinking of alkyds, i.e., linoleic acid esters, where the ester residue is represented by R. It should be understood that this diagram is merely illustrative, and that any unsaturated alkyd resin or mixture of different alkyd resins can be used. In the oxidative crosslinking diagram below, (1) represents the actual oxidation with O2, (2) represents initiation with a Co(II) salt, such as a Me(II) salt or cobalt dichloride, (3) represents chain propagation with another linoleic acid ester molecule, and (4) represents termination. [ka] Reaction Scheme 1 : An example of oxidative crosslinking of alkyd resins using linoleic acid esters

[0050] Scheme 2 shows the formation of undesirable cleavage products, particularly strong-smelling short-chain cleavage products, from alkyd resins by oxidative crosslinking using the above linoleic acid ester (having the ester residue R). (1) shows the addition of O2 to the linoleic acid ester molecule, (2) shows the formation of free radicals by the elimination of OH radicals, and (3) shows the formation of short-chain aldehydes and esters with terminal double bonds by cleavage. [ka] Reaction Scheme 2 : Example of formation of cleavage products by oxidative crosslinking of alkyd resins with linoleic acid esters

[0051] Equation 3 shows the Diels-Alder reaction, which occurs between the first and second molecules in the corrosion inhibitors of the present invention. Here, dicyclopentadiene reacts with the double bond of linseed oil, which acts as a dienophile. It can be seen that dicyclopentadiene reacts with various double bonds in linseed oil to form a (substituted) norbornene ring system. The double bonds produced by the Diels-Alder reaction can contribute to oxidative crosslinking of alkyd resins. The double bonds in this (substituted) norbornene ring system are also susceptible to oxidative cleavage. However, even if the double bond is cleaved by oxidative cleavage, short-chain aldehydes are not produced because the (substituted) norbornene exists as a bicyclic substance. [ka] Reaction Scheme 3 : Example of the reaction of alkyd resin with dicyclopentadiene (DCPD) at linoleic acid residues

[0052] The substituted 1,3-butadienes are preferably in the s-cis configuration.

[0053] The term "s-cis configuration" is known to those skilled in the art and refers to the fact that the double bond between C1 and C2 and the double bond between C2 and C3 of the substituted 1,3-butadiene are in a cis configuration with respect to the single bond between C2 and C3 of the substituted 1,3-butadiene. In the present invention, existence in the s-cis configuration includes the predominant, preferably stable, existence of the substituted 1,3-butadiene in the s-cis configuration, i.e., the free rotation about the C2-C3 single bond is either completely lost, as in the case of, for example, cyclopentadiene (or dicyclopentadiene) or 1,3-cyclohexadiene, or is at least sterically favored by the presence of corresponding residues / substituents on the substituted 1,3-butadiene.

[0054] The s-cis conformation is advantageous because it results in a planar structure in which the four carbon atoms of 1,3-butadiene lie in a plane. However, it will be apparent to those skilled in the art that a slight torsion angle, e.g., less than 30°, preferably less than 15°, reduces the reactivity of the diene with respect to reaction with dienophiles, but does not necessarily prevent this reaction.

[0055] As the substituted 1,3-butadiene, any substituted 1,3-butadiene can be used. The molecular weight of the substituted 1,3-butadiene is preferably greater than 54.9 g / mol (i.e., greater than the molecular weight of 1,3-butadiene) and 250 g / mol or less, more preferably 60 g / mol to 150 g / mol, 70 g / mol to 120 g / mol, 80 g / mol to 110 g / mol, or 90 g / mol to 100 g / mol. By using a relatively small diene, i.e., a diene having a molecular weight within the above range, the reaction between the diene and the unsaturated compound (dienophile) can be reliably carried out.

[0056] Preferably, the substituted 1,3-butadiene is a cyclic compound, more preferably cyclopentadiene and / or 1,3-cyclohexadiene. Cyclopentadiene is especially preferred.

[0057] At room temperature, cyclopentadiene exists in the form of a dimer, dicyclopentadiene (DCPD). At high temperatures, the two forms are in equilibrium. Therefore, the terms cyclopentadiene and dicyclopentadiene are interchangeable and used interchangeably in the present invention. Cyclopentadiene / dicyclopentadiene is particularly preferred in the present invention because it is highly reactive and easy to handle.

[0058] It is clear that any cyclic compound in which the substituted 1,3-butadiene is in the s-cis configuration can be used, and these cyclic compounds may have additional substituents or residues, preferably at the C1 or C1 and C4 positions of the 1,3-butadiene structure, or at one or more other positions in the ring system.

[0059] Instead of cyclopentadiene or cyclohexadiene, for example, a substituted cyclopentadiene or cyclohexadiene may be used. In this case, one or more residues having a +I effect, more preferably a +M effect, are preferably used as the substituent. A preferred example of a substituted cyclopentadiene that is more reactive than unsubstituted cyclopentadiene is 1-methoxy-1,3-cyclopentadiene.

[0060] The substituted 1,3-butadiene preferably has a moiety that increases the electron density in the conjugated double bond of the substituted 1,3-butadiene, and this moiety preferably has a +I effect or a +M effect and is located at the C1 position of the substituted 1,3-butadiene or at the C1 and C4 positions of the substituted 1,3-butadiene.

[0061] Such substituents that increase the electron density within the conjugated double bond of substituted 1,3-butadienes, including positions within / relative to the 1,3-butadiene, are known to those skilled in the art.

[0062] Preferred radicals herein are those with a positive inductive effect (+I effect) or a positive mesomeric effect (+M effect). Both have an electron transfer effect, which increases the electron density in the conjugated double bonds of substituted 1,3-butadienes. The electron transfer effect of the +M effect is generally greater than that of the +I effect. Increasing the electron density in the conjugated double bonds of substituted 1,3-butadienes increases the reactivity of the diene in the Diels-Alder reaction. Therefore, the time course and degree of reaction of the diene with the dienophile, i.e., the proportion of the dienophile that reacts with the diene, can be controlled.

[0063] Examples of radicals with a +I effect include alkyl radicals such as the methyl radical, the ethyl radical, the n-propyl radical, the i-propyl radical, the n-butyl radical, or the t-butyl radical.

[0064] Examples of radicals having a +M effect include the NH2 radical, the NR2 radical, the OH radical, the OR radical, the NH(CO)R radical, the O(CO)R radical, a substituted aryl radical, a phenyl radical, and a halogen radical such as bromine, chlorine, iodine, or fluorine. The substituent of the R or substituted aryl radical is preferably an alkyl radical having a +I effect, in particular one of the radicals exemplified above.

[0065] Preferably, the resin has multiple double bonds, more preferably, multiple lone double bonds, and even more preferably, at least one conjugated double bond. Suitable resins that can be used in the present invention are as described and exemplified above. In particular, conjugated acids, i.e., conjugated fatty acids such as conjugated linoleic acid, are preferably used in the present invention.

[0066] Due to the presence of multiple double bonds in the unsaturated compound, sufficient steric crosslinking of the composition is achieved more completely and in some cases more quickly.

[0067] As used herein, the term "multiple isolated double bonds" refers to a group of double bonds known to those skilled in the art that are not clustered or conjugated and have at least one sp 3 This refers to double bonds that are separated from each other by hybridized C atoms. The presence of multiple isolated double bonds can result in a polyester or alkyd resin with multiple reactivities. For example, the presence of clustered double bonds means that the polyester or alkyd resin will not react with dienes as a dienophile. The same is true for conjugated double bonds, which can react with the double bonds of substituted or unsubstituted 1,3-butadiene, a dienophile, as a diene. At the very least, clustered and conjugated double bonds are considered to have low reactivity with dienes.

[0068] Those skilled in the art can use frontier orbital theory (see D.I. Schuster, T.M. Weil; J. Am. Chem. Soc., 95-12 (1973), 4092-94) to qualitatively and quantitatively predict or estimate the reactivity of dienes with dienophiles. In particular, frontier molecular orbital / FMO theory can be used to predict or estimate. Therefore, based on the structures of the reactants used, those skilled in the art can predict whether and how a Diels-Alder reaction will occur. As a result, the reaction rate of the Diels-Alder reaction can be determined, and which compounds act as dienes and which compounds act as dienophiles. Based on this, those skilled in the art can easily determine which dienes will react with a given dienophile to cause a Diels-Alder reaction.

[0069] To enhance the reactivity of each reactant in the Diels-Alder reaction, a Lewis acid may be added. Examples of Lewis acids that can be used for this purpose include B(CH3)3, B(OH)3, BF3, AlCl3, CO2, SO3, SiCl4, or BF5 (see KN Houk, J. Am. Chem. Soc., 95 (1973), 4094-96 and EJ Corey et al., J. Am. Chem. Soc., 126 (2004), 13708-13713).

[0070] In the present invention, it has been found that the use of one or more conjugated double bonds in the first molecule partially or preferably completely prevents the formation of strong-smelling compounds, particularly the formation of short-chain aldehydes or short-chain carboxylic acids, particularly aldehydes or carboxylic acids having 3 to 9 carbon atoms, e.g., 4 to 8 carbon atoms, 5 to 7 carbon atoms, or 6 carbon atoms, thereby reducing emissions. In the present specification, it is not necessary to perform a Diels-Alder reaction on the first molecule.

[0071] It is further understood that the Diels-Alder reaction does not have to be with the resin, but can be with its precursor. For example, an unsaturated fatty acid with double allylic hydrogen atoms can be subjected to a Diels-Alder reaction prior to forming a triglyceride. However, it is generally preferred to perform a Diels-Alder reaction with the resin.

[0072] The composition may also include an anti-drip additive.

[0073] The anti-drip additive is a solid polymer or wax particle with a low softening point. The corrosion inhibitor containing the anti-drip additive can be sprayed onto the desired part, particularly an automotive part. After the anti-corrosion agent is dripped, the next processing step involves briefly heating the part to a temperature of 50°C to 80°C, preferably at least 55°C. This heating brings the sprayed part to its drop-off point. This heating softens the anti-drip additive dispersed in the anti-corrosion agent. This results in an increase in the gelation / viscosity of the corrosion inhibitor, which solidifies to a gel-like consistency. This solidification prevents unwanted dripping of the anti-corrosion agent during subsequent processing steps.

[0074] Preferably, the composition comprises further additives, for example corrosion protection additives such as calcium sulfonate, flexibility imparting agents (internal plasticizers) such as mineral oil, fillers such as talc, kaolin, aluminum hydroxide, silicates or calcium carbonate, rheological additives such as inorganic thickeners, for example layered silicates such as bentonite, organic or inorganic bases such as triethylenediamine which also contribute to corrosion protection, catalysts for oxidative hardening of the corrosion inhibitors, for example manganese salts, and other ingredients, for example ingredients which prevent film formation on standing, such as 2-butanone oxime (MEKO). Similarly, colorants, in particular pigments, can be incorporated into the corrosion inhibitors.

[0075] In the present invention, the amounts indicated in parts by weight are each based on 100 parts by weight of the prepared corrosion inhibitor, i.e., the corrosion inhibitor into which all necessary components and, if necessary, additives have been mixed.

[0076] The first molecule, and if applicable, the first molecule and the second molecule, are preferably contained in an amount of 2 to 20 parts by weight, preferably 4 to 15 parts by weight, per 100 parts by weight of the composition.

[0077] The composition is applied to the part in a wet film thickness of 40 μm to 1,000 μm. Preferably, the wet film thickness is 50 μm to 950 μm, e.g., 100 μm to 900 μm, 150 μm to 850 μm, 200 μm to 800 μm, 250 μm to 750 μm, 300 μm to 700 μm, 350 μm to 650 μm, 400 μm to 600 μm, 450 μm to 550 μm, or 500 μm to 520 μm.

[0078] The wet film thickness is related to the coating method selected: the composition is applied to the part in a wet state, and the film thickness is determined by the selected application method, which has the advantage that the film thickness can be determined immediately without waiting for the film to dry completely.

[0079] Application may be carried out, for example, with a squeegee, such as a spiral squeegee (manufactured by BYK-Chemie), or with a cup gun, such as a SataJet®, having a suitable nozzle opening, such as 0.8 mm to 1.2 mm, and air pressure at a suitable spray pressure, such as 3.5 bar. This nozzle opening and spray pressure are suitable for a wet film thickness in the range of 40 to 1,000 μm. The wet film thickness is determined by applying a specific amount of the composition.

[0080] The coating thus applied is dried for 72 hours in a two-stage process, preferably in a manner similar to that described in paragraphs

[0005] and

[0006] . After drying, it can be subjected to a corrosion test. Herein, the corrosion protection properties of the composition are measured on various substrates, preferably according to DIN EN ISO 9227. The substrates used are materials that are standard in automotive manufacturing. For example, the steel substrate used is Q-Panel R-36 (manufactured by Q-Lab Deutschland GmbH, In den Hallen 30, D-66115 Saarbrücken, Germany, size 76 mm x 152 mm, thickness d = 0.81 mm).

[0081] According to one embodiment of the present invention, the molecule without double allylic hydrogen atoms is a first molecule, the plurality of molecules with double allylic hydrogen atoms are second molecules, and the ratio of the number of first molecules to the number of second molecules is at least 100.

[0082] It will be apparent to those skilled in the art that the terms "molecule" or "first molecule" are interchangeable. Thus, a molecule or a first molecule is the same compound. For ease of distinction only, when a second molecule is used, it is referred to as a first molecule.

[0083] The ratio of the number of first molecules to the number of second molecules is preferably at least 200, e.g., at least 300, at least 400, at least 500, at least 10 3 , at least 10 4 , more preferably at least 10 5 By reducing the content of the second molecule, the emissions / odor generated by oxidative crosslinking can be reduced.

[0084] According to another embodiment of the present invention, the resin is a modified resin, the modified resin having a reduced number of double allylic hydrogen atoms compared to before modification.

[0085] The number of double allylic hydrogen atoms can be reduced in a similar manner as described above.

[0086] According to one embodiment of the present invention, the composition comprises 5 to 20% by weight of the resin, based on 100% by weight of the corrosion inhibitor for cavity sealing or bottom protection with reduced odor and emissions. Preferably, the resin is selected from the group consisting of unsaturated polyesters, unsaturated alkyd resins and unsaturated binders.

[0087] According to another embodiment of the present invention, the resin does not include an acrylic resin and / or an epoxy resin.

[0088] According to one embodiment of the present invention, the composition comprises 2 to 8% by weight, preferably 3.5 to 4.5% by weight, of wax relative to 100% by weight of the composition.

[0089] Preferably, said wax is selected from the group consisting of mineral / fossil / natural waxes, in particular kerosene waxes, semi-synthetic waxes, synthetic waxes and microcrystalline waxes.

[0090] According to another embodiment of the invention, the composition comprises 40 to 70% by weight, preferably 48 to 55% by weight, of oil relative to 100% by weight of the composition.

[0091] Preferably, the oil is selected from the group consisting of mineral oils, in particular mineral oils having a cut number of 75 to 300. More preferably, the cut number is 100 to 275, for example 125 to 250, 150 to 225, or 175 to 200.

[0092] According to one embodiment of the present invention, after reaction, the reduced odor and emissions cavity sealing or bottom protection corrosion inhibitor exhibits no detectable change when exposed to temperatures of 70°C or higher for 5 minutes to 2 hours and / or temperatures of -15°C or lower for 5 minutes to 2 hours.

[0093] According to another embodiment of the present invention, the odor and emission reduced cavity sealing or bottom protection corrosion inhibitor comprises at least one short-chain aldehyde and / or at least one short-chain carboxylic acid at a concentration of less than 100 ppm.

[0094] Preferably, the carbon number of the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid is 3 to 9. More preferably, the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid is formed by crosslinking over time.

[0095] According to yet another embodiment of the present invention, the concentration of the at least one short-chain aldehyde (preferably having 3 to 9 carbon atoms) and / or the at least one short-chain carboxylic acid (preferably having 3 to 9 carbon atoms) is less than 40 ppm, preferably less than 25 ppm, more preferably less than 20 ppm, less than 15 ppm, less than 10 ppm, less than 5 ppm, or less than 1 ppm.

[0096] The concentration of the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid can be measured by any suitable method, such as chromatographic methods, in particular gas chromatography or HPLC, and / or mass spectrometry. Preferably, the concentration of the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid is measured according to the method described in the Examples.

[0097] Particularly preferably, the concentration of the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid at the time of application is equal to or less than the applicable maximum working environment concentration, which is determined in accordance with applicable legal requirements, such as those of the European Union (including listed facilities, chemicals, etc.), thereby ensuring sufficient protection for employees.

[0098] Preferably, the concentration of said at least one short-chain aldehyde is measured according to DIN ISO 16000-6:2012-11.

[0099] According to yet another embodiment of the present invention, the reduced odor and emission corrosion inhibitor for cavity sealing or bottom protection has a rating of less than 3, preferably less than 2, more preferably 1 in the odor test according to VDA 270 and / or PV 3900. Thus, the user will only be slightly, and preferably will not be, bothered by the odor of the at least one short-chain aldehyde and / or the at least one short-chain carboxylic acid, if any.

[0100] Preferably, the odor test is carried out according to the method described in the Examples.

[0101] Preferably, the corrosion inhibitor is a so-called solvent-borne cavity protectant or a 100% cavity protectant. Compared to so-called water-soluble cavity protectants, these cavity protectants do not contain water, or if they do contain water, the water content is low (for example, a water content of less than 5% by weight, preferably less than 1% by weight, or less than 0.1% by weight, based on 100% by weight of the composition). Solvent-borne cavity protectants or 100% cavity protectants are characterized by faster and more uniform drying than water-soluble cavity protectants.

[0102] According to one embodiment of the present invention, the part is a vehicle part. Preferably, the part is selected from the group consisting of automobile parts, railroad vehicle parts, commercial vehicle parts, agricultural machinery parts, forestry machinery parts, construction machinery parts, aircraft parts, and marine vessel parts. More preferably, the part is an automobile part.

[0103] Generally, the corrosion inhibitor of the present invention may be applied to any part, cavity, or underside of an automobile, and may be applied to a portion or the entire surface of the part, for example, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or 95% or more of the entire surface of the part.

[0104] Preferably, said part is a technical part, i.e. a part that is not used in construction, more preferably said part is an automotive part in a hollow or bottom part.

[0105] The part may also be a metal part, for example a part made of a metal alloy, preferably steel, or a part made of a fiber reinforced composite material, for example a part made of CFRP (carbon fiber reinforced plastic).

[0106] A method for applying an anti-corrosion coating to a component can include (a) applying a composition to the component, and (b) drying the composition.

[0107] Preferably, the part to which said composition is applied or coated is obtained by the method according to the invention.

[0108] Preferably, after step (a) of applying the anti-corrosion agent to the component and before step (b) of drying the anti-corrosion agent, step (a1) of allowing the anti-corrosion agent to penetrate the component and, if necessary, step (a2) of wiping off excess anti-corrosion agent from the component are carried out.

[0109] As mentioned above, the use of Diels-Alder products can reduce and, if necessary, completely avoid emissions and odor problems not only during the actual manufacturing process but also in the finished anti-corrosion coating. This has the advantage that the odor of the finished vehicle can be more easily controlled by the vehicle manufacturer or purchaser in any way desired.

[0110] It is understood that the features mentioned above and those to be described below may not only be used in the combination indicated in each case, but may also be used in other combinations or alone without departing from the scope of the invention. [Example]

[0111] The present invention will be described in more detail below with reference to examples.

[0112] Example 1 The odor evaluation method for corrosion inhibitors is shown below. I. Objective and Scope: This method was developed in accordance with VDA 270 / PV 3900 and is used to evaluate the odor behavior of corrosion inhibitors, especially HRK materials, under the influence of temperature. II. Definition: Odor behavior is understood to describe the tendency of a substance to produce volatile compounds that result in a perceptible odor. III. Principle: After pretreatment and temperature exposure, the odor is olfactory evaluated by at least three selected odor panelists. Five odor panelists are recommended. IV. Equipment used: Laboratory stirrer, e.g. IKA stirrer 20.n with tilted blades, four stainless steel blades Cold-rolled steel sheet or clean, odor-free aluminum foil (approximately 10cm x 20cm) Odor-free, clean aluminum foil Aluminum dish: Storage container φ64 mm; Model: 550028; Material No.: 3201964; Novelis Germany GmbH Use a 1 L glass container with an odor-free seal and lid as the test device, for example a 1 L storage container from Frucht & Fun. Air-circulating heating chamber (drying oven), e.g. Heraeus UT 6200. V. Experiment V.1 Sample Preparation a) Spray wax -Sample material (viscous cavity protectant) for 1000 min -1 Stir at room temperature for 15 minutes. The sample material is applied to a steel sheet or aluminum foil (10 cm x 20 cm) using a film drawing frame with a wet film thickness of 200 μm. Activate the sample in a drying oven at 65°C for 5 minutes. ·Precondition the sheet at (23±2)℃ and (50±5)% relative humidity for 7 days. Apply (100±5) mg of the dried sample to a piece of aluminum foil (5 cm x 5 cm) with a spatula. A 5cm x 5cm piece of aluminum foil is placed at the bottom of the test container together with (100±5) mg of dry sample and sealed. b) Immersion wax Weigh out 1g of sample material into an aluminum dish (a storage container with a diameter of 64mm). Place the aluminum dish with 1g of sample material at the bottom of the test vessel and cover. c) Raw materials Weigh out 1g of sample material into an aluminum dish (a storage container with a diameter of 64mm). Place the aluminum dish with 1g of sample material at the bottom of the test vessel and cover.

[0113] V.2 Storage conditions and odor test All tests listed in the table below will be performed. a) Spray wax [Table 1-1] b) Immersion wax [Table 1-2] c) Raw materials [Table 1-3] Remarks The odor assessment is carried out immediately after the test container is removed from the drying oven, after which the test container is reclosed. Re-evaluate the odor of the test container in a) after storing it at room temperature for one day. The containers are then stored under the same conditions as in condition 2.1 and the evaluations described in a) and b) are carried out. The containers are then resealed and stored at 105°C (condition 2.2). After a further 7 days of storage at room temperature, an odor evaluation is carried out. After removal from the oven, the test containers are allowed to cool for 5 minutes and then evaluated olfactorily. VI. Odor evaluation The odor assessment is carried out according to the current VDA 270. All possible conditions are assessed using the criteria listed in Table 1.4. The assessment is made on a scale of 1 to 6, with an option to assess in 0.5-point increments. [Table 1-4]

[0114] The odor behavior evaluation results are expressed as arithmetic averages, rounded to the nearest 0.5 point.

[0115] Example 2 The following is another method for assessing corrosion inhibitor emissions.

[0116] I. Purpose and Scope This method is used to clarify the types and amounts of gas-releasing organic substances made from non-metallic materials used in vehicle interiors. Each substance is quantified in terms of toluene.

[0117] II. Principle To perform the sampling, the material is placed in a micro-test chamber set at a constant temperature and flow rate. Analytes collected on Tenax TA® are thermally extracted. The analytes (emissions) are then separated by gas chromatography and detected by mass spectrometry. The measurements obtained with this test method are valid only under the conditions described herein. The results are not suitable for health assessment of the detected substances. Furthermore, the results are not suitable for estimating total emissions for the entire vehicle. III. Equipment Micro-Chamber / Thermal Extractor™ (µ-CTE™); 6-chamber model; Marks International Rotilabo® aluminum dish with handle; φ28 mm, 8 mL; Order No. PP54.1; Carl Roth GmbH & Co. KG Glass tubing; 1 / 4" x 3 1 / 2"; Tenax TA; C6-C30; Conditioned & Capped; Product Number: C1-BAXX-5039; Marks International FlowMark™ Flow Meter; 0.5 mL / min to 500 mL / min; Product Number: N9307086; PerkinElmer TD 100xr; Thermal Desorber; Marks International Cold trap, general-purpose hydrophobic; Item No.: U-T2GPH-2S; QC: QQR-0145 GCMS 2010; Shimadzu Corporation ·GCMS QP 2010; Mass spectrometer; Shimadzu Corporation Standard injection microsyringe, e.g., 5 μL syringe; SGE Analytical Sciences IV. Experiment IV.1 Sample preparation a) Spray wax -Sample material (viscous cavity protectant) for 1000 min -1 Stir at room temperature for 15 minutes. Accurately weigh out approximately 150 mg of sample material into an aluminum dish (Rotilabo (registered trademark) aluminum dish with handle; φ28 mm) (mark the aluminum dish with a sharp object such as tweezers). Activate the sample in a drying oven at 65°C for 5 minutes. · Precondition the aluminum dish at (23±2)℃ and (50±5)% relative humidity for 7 days. b) Immersion wax Accurately weigh out approximately 150 mg of sample material into an aluminum dish (Rotilabo (registered trademark) aluminum dish with handle; φ28 mm) (mark the aluminum dish with a sharp object such as tweezers). c) Raw materials (If liquid) Sample material: 1000 min-1 Stir at room temperature for 15 minutes. Accurately weigh out approximately 150 mg of sample material into an aluminum dish (Rotilabo (registered trademark) aluminum dish with handle; φ28 mm) (mark the aluminum dish with a sharp object such as tweezers). The sample may be activated in a drying oven at 65°C for 5 minutes (see IV.3 Test Method). The aluminum dish may be preconditioned at (23±2)°C and (50±5)% relative humidity for 7 days (see IV.3 Test Method).

[0118] IV.2 Sampling Sampling is performed using a Micro-Chamber / Thermal Extractor™ (µ-CTE™). Before use, the µ-CTE™ is rinsed with isopropanol. After rinsing, the chamber is heated to a maximum temperature of 120°C for 30 minutes to completely remove the isopropanol, and the flow rate is set to approximately 40 mL / min. A PerkinElmer FlowMark™ is used to set and check the flow rate. Analytes are collected in glass tubes filled with Tenax TA (TD tubes). These TD tubes are conditioned before use to remove any residue from previous analyses. Conditioning is performed as described in Section IV 4.4. For each sampling, a TD tube is attached to the outlet of the µ-CTE™.

[0119] All samples are run alongside a control sample as a reference, since comparative evaluation with the co-run sample is always required. Sampling parameters are shown in Table 2.3. As a rule, test condition 1 is used. Test condition 2 is only used when an increase in signal (obtained from condition 1) is required or when required by customer specifications. a) Spray wax [Table 2-1] b) Immersion wax [Table 2-2] c) Raw materials [Table 2-3] IV.3 Test Method a) Activate the sample in a drying oven at 65°C for 5 minutes. b) Precondition the aluminum dish at (23±2)°C and (50±5)% relative humidity for 7 days.

[0120] IV.4 Analysis of Samples Analytical separation of the samples is performed by gas chromatography (GCMS 2010). Samples are introduced using a thermal desorber (TD 100xr). Detection is performed using a mass spectrometer (GCMS QP 2010). All sample measurements are performed using the instrument parameters listed in IV.4 Sample Analysis, Tables 2.4-2.10. Once a week, the gas chromatograph should be autotuned to ensure optimal detector voltages and to check the system's tightness. Each measurement is always performed using the latest Auto-Tune version.

[0121] IV.4.1 Thermal desorption Thermal desorption is performed using a Marks International TD 100xr instrument. A "general-purpose hydrophobic" cold trap is used. This cold trap is designed for the analysis of VOCs (volatile organic compounds) in the C4 / 5 to C30 / 32 range. [Table 2-4] [Table 2-5] [Table 2-6] [Table 2-7] [Table 2-8] [Table 2-9]

[0122] IV.4.2 Chromatography Gas chromatographic separation was performed using a Shimadzu GCMS 2010. A Macherey-Nagel Optima 5 MS column (50.0 m long, 5.00 μm thick, 0.32 mm diameter) or equivalent was used. The initial oven temperature was 40°C, and the equilibration time was 3.00 min. [Table 2-10] IV.4.3 Mass spectrometer A GCMS QP 2010 mass spectrometer (Shimadzu Corporation) was directly connected to the gas chromatograph. This mass spectrometer was a quadrupole mass spectrometer (MS) equipped with an electron impact ionization source. [Table 2-11]

[0123] IV.4.4 Adjustment of the thermal desorption tube The TD tube is conditioned directly in the thermal desorber, applying the parameters shown in Tables 2.12, 2.13 and 2.14. [Table 2-12] [Table 2-13] [Table 2-14]

[0124] V. Calibration V.1 Preparation of calibration solutions To perform the calibration, prepare a calibration solution containing 0.5 μg / μL toluene in methanol. Accurately weigh approximately 25 mg of toluene (pa) into a 50 mL volumetric flask and make up to 100% with methanol (pa). This solution has a shelf life of 3 months when stored in the refrigerator. Attach a label to the prepared solution indicating the date of manufacture, contents, and expiration date.

[0125] V.2 Measurement of calibration solutions The calibration solution is allowed to return to room temperature. For measurement, 4 μL of the calibration solution is added directly to the thermal desorption tube filled with Tenax TA using a micropipette. The calibration solution is dispensed into the thermal desorption tube as indicated by the arrow.

[0126] Then, an inert gas (helium or nitrogen) is passed through the TD tube at a flow rate of approximately 1 L / min to 3 L / min for 1 minute. This allows the analyte to be adsorbed onto Tenax-TA®, significantly reducing the amount of excess solvent (methanol). The measurement is carried out in the same manner as the sample measurement (see Section IV). Measurements are carried out in triplicate.

[0127] V.3 Evaluation and calculation of response factors The evaluation is performed using the peak area. The toluene peak is integrated (link point) to determine the area. This is performed for all three measurements. The response factor is then calculated using the determined peak area using Equation 1.

number

[0128] VI. Emissions Assessment The amount of released material is evaluated according to each question. In each case, the aldehyde and carboxylic acid peaks are evaluated. The total amount of organic compounds (TVOC) in the entire chromatogram is also evaluated. In each case, the amount of released material is expressed as toluene equivalent (μg) / sample weight (g). The toluene equivalent is calculated from the peak area and the previous calibration (see Section 0). The evaluation of each sample is always performed by comparison with a control sample that was measured together. The amount of released material is calculated using Equation 2. The response factor (Rf value) is calculated by calibration (see Section 0).

number

[0129] Example 3 The ingredients (weight percent) of three example 100% cavity protectants (HRK) are shown below in Table 3.1.

[0130] Here, "100%HRK" is a conventional cavity protectant that uses soybean oil as an alkyd resin. 100%HRK1 and 100%HRK2 are cavity protectants according to the present invention, one of which is a Diels-Alder reaction product of soybean oil and cyclopentadiene (100%HRK1) and the other is a product that uses an alkyd resin primarily containing conjugated double bonds (100%HRK2). [Table 3]

[0131] Example 4 Odor measurement results for 100% HRK, 100% HRK1 and 100% HRK2 in Example 3 using the measurement methods in Example 1 (Table 4.1) and Example 2 (Table 4.2). [Table 4-1] [Table 4-2]

[0132] Table 4.1, and especially Table 4.2, show that the use of corrosion inhibitors according to the invention reduces odors and emissions, in some cases significantly, due to the reduced production of short-chain aldehydes.

Claims

1. 1. Use of a corrosion inhibitor composition for cavity sealing or bottom protection of a part with reduced odor and emissions, comprising: the composition comprises a resin, the resin comprises a plurality of molecules, the plurality of molecules comprises molecules that do not have double allylic hydrogen atoms; The composition is applied to the part at a wet film thickness of 40 μm to 1,000 μm; the resin is a modified resin, and the modified resin has a reduced number of double allylic hydrogen atoms compared to before modification; and The part is a vehicle part.

2. The molecule that does not have a double allylic hydrogen atom is a first molecule, and the plurality of molecules includes a second molecule that has a double allylic hydrogen atom, and the ratio of the number of first molecules to the number of second molecules is at least 10 3 2. The use according to claim 1, characterized in that

3. 2. Use according to claim 1, characterized in that the composition comprises 5 to 20% by weight of said resin relative to 100% by weight of corrosion inhibitor for cavity sealing or bottom protection with reduced odor and emissions.

4. 2. The use according to claim 1, characterized in that the resin does not comprise an acrylate resin and / or an epoxy resin.

5. 2. Use according to claim 1, characterized in that the composition comprises from 2 to 8% by weight of wax relative to 100% by weight of the composition.

6. 2. Use according to claim 1, characterized in that the composition comprises from 40 to 70% by weight of oil relative to 100% by weight of the composition.

7. 2. The use according to claim 1, characterized in that after the oxidative crosslinking reaction of the resin to obtain the cured corrosion inhibitor with reduced odor and emissions, the cured corrosion inhibitor with reduced odor and emissions for cavity sealing or bottom protection exhibits no detectable change when exposed to a temperature of 70°C or higher for 5 minutes to 2 hours and / or to a temperature of -15°C or lower for 5 minutes to 2 hours.

8. 2. The use according to claim 1, characterized in that the concentration of at least one short-chain aldehyde and / or at least one short-chain carboxylic acid contained in the corrosion inhibitor for cavity sealing or bottom protection with reduced odor and emissions is less than 100 ppm.

9. 9. Use according to claim 8, characterized in that the concentration of said at least one short-chain aldehyde and / or said at least one short-chain carboxylic acid having 3 to 9 carbon atoms is less than 40 ppm.

10. 2. The use according to claim 1, characterized in that the odor- and emission-reducing corrosion inhibitor for cavity sealing or bottom protection has a rating of less than 3 in the odor test according to VDA 270 and / or PV 3900.

Citation Information

Patent Citations

  • Method for forming corrosion-proof film

    JP1986107981A

  • Rust-proofing agent

    JP1988258972A

  • Rust preventive composition for underfloor of automobile

    JP1993195261A

  • Cyclopentadiene-modified alkyd resin

    JP1993339352A

  • Compositions containing cyclopentadiene adducts and their use for chemical resistant coatings

    JP2005517075A